Case report: A double pathogenic mutation in a patient with late-onset MELAS/PEO overlap syndrome - Zhao, Qiu Yan; Zhang, Wen Zhao; Zhu, Xue Lian; Qiao, Fei; Jia, Li Yuan; Li, Bi; Xiao, Yong; Chen, Han; Zhang, Yu; Chen, Yun Guo; Wang, Yong Liang (Frontiers in Neurology, 2022)
Mitochondrial encephalopathy, lactic acidosis and stroke-like episodes (MELAS) and progressive external ophthalmoplegia (PEO) are established phenotypes of mitochondrial disorders. They are maternally inherited, multisystem disorder that is characterized by variable clinical, biochemical and imaging features. We described the clinical and genetic features of a Chinese patient with late onset MELAS/PEO overlap syndrome, which has rarely been reported. The patient was a 48-year-old woman who presented with recurrent ischemic strokes associated with characteristic brain imaging and bilateral ptosis. We assessed her clinical characteristics and performed mutation analyses. The main manifestations of the patient were stroke-like episodes and seizures. A laboratory examination revealed an increased level of plasma lactic acid and a brain MRI showed multiple lesions in the cortex. A muscle biopsy demonstrated ragged red fibers. Genetic analysis from a muscle sample identified three mutations; TL1 m.3243A>G and POLG c.3560C>T, with mutation loads of 83% and 43%, respectively. This suggested that mitochondrial disorders are associated with various clinical presentations and an overlap between the syndromes and whole exome sequencing is important, as patients may carry multiple mutations.